Making the material routine: a sociomaterial study of the relationship between police body worn cameras (BWCs) and organisational routines. (2nd January 2021) - Guzik, Keith; Sesay, A.; Oh, O.; Ramirez, R.; Tong, T.
ABSTRACT: This article employs a sociomaterial perspective adapted from information systems and management studies to examine the potential impact of body worn cameras (BWCs) on police organisations. Based on 42 semi-structured interviews with police employees, the study illustrates how wearable camera technology is seen to 'afford' officers and agencies the ability to modify their work routines. Further, these modifications occur in conjunction with particular dimensions of body camera system's material agency. Through the performativity of video recording devices to move, see, hear, and record, officers report altering how they approach patrol work by displacing certain tasks onto their material associates, which allows them to better carry out their duties. Through the interoperability of the cloud storage systems, departments describe being able to reorganise critical information processing routines in support of criminal prosecutions. Through the objectivity of the digital files produced by body-worn camera systems, departments note effortlessly creating packets of events bearing the impression of truth and legitimacy with which they are able to more easily resolve citizen complaints. These findings underscore the importance of remaining attentive to the materiality of technology in policing and law enforcement research.